Chinese Students' Higher Achievement in Mathematics Comparison of Mathematics Education of Australian and Chinese Primary Schools / by Dacheng Zhao. - Zhao, Dacheng. (Mathematics Education – An Asian Perspective, 2016)
This book shares insights into the achievement gap in mathematics between East Asian and Western countries, and the ways to improve students’ mathematics achievements. Especially, it highlights the importance to integrate case studies with large-scale international comparative studies in general, and comparative studies of mathematics education in particular. This book is a must-read for mathematics teachers, mathematics educators, educational researchers, education administrators, curriculum developers, assessment designers, and student teachers who are interested in mathematics education and how to improve students’ mathematics achievements.